The 1840 Census of Charles County, Maryland - the Sixth Census - Schuhart, Wanda A. (Transcriber); Peggy W. Schindler (Transcriber) (Printing Press Leonardtown, MD, 2002)
Transcribed by Wanda A. Schuhart and Peggy W. Schindler for the St. Mary's County Historical Society